Fracture Related Infections and Their Risk Factors for Treatment Failure—A Major Trauma Centre Perspective - Victor Lu; James Zhang; Ravi Patel; Andrew Kailin Zhou; Azeem Thahir; Matija Krkovic (Diagnostics, 2022)
Fracture related infections (FRI) are debilitating and costly complications of musculoskeletal trauma surgery that can result in permanent functional loss or amputation. Surgical treatment can be unsuccessful, and it is necessary to determine the predictive variables associated with FRI treatment failure, allowing one to optimise them prior to treatment and identify patients at higher risk. The clinical database at a major trauma centre was retrospectively reviewed between January 2015 and January 2021. FRI treatment failure was defined by infection recurrence or amputation. A univariable logistic regression analysis was performed, followed by a multivariable regression analysis for significant outcomes between groups on univariable analysis, to determine risk factors for treatment failure. In total, 102 patients were identified with a FRI (35 open, 67 closed fractures). FRI treatment failure occurred in 24 patients (23.5%). Risk factors determined by our multivariate logistic regression model were obesity (OR 2.522; 95% CI, 0.259–4.816; p = 0.006), Gustilo Anderson type 3c (OR 4.683; 95% CI, 2.037–9.784; p = 0.004), and implant retention (OR 2.818; 95% CI, 1.588–7.928; p = 0.041). Given that FRI treatment in 24 patients (23.5%) ended up in failure, future management need to take into account the predictive variables analysed in this study, redirect efforts to improve management and incorporate adjuvant technologies for patients at higher risk of failure, and implement a multidisciplinary team approach to optimise risk factors such as diabetes and obesity.